Policy and technology for rice productivity growth in Asia - Rosegrant, Mark W.; Pingali, Prabhu L. (Wiley, 1994)
In the past decade, declining rice prices, a slowdown in research expenditures and output growth, reduced irrigation investment and degradation of irrigated land, declining marginal returns to input use, and a stagnant technological yield frontier caused declining growth in rice yields per hectare in much of Asia. Future growth in rice productivity will increasingly come from improved management and efficiency of use of the resources utilized in rice production, in contrast to the rapid dissemination of modern technology which has been dominant in the past. The foundations for increased efficiency in rice production are greater investment in research, extension, and education to upgrade human capital, combined with establishment of economic incentives that reflect the social opportunity costs of scarce resources.